Patient (pt) experience with a smartphone application (app) and biosensor for remote symptom monitoring during systemic cancer therapy: Qualitative findings from initial testing. Issue 28 (1st October 2022) - Ramsey, Scott David; Shankaran, Veena; Bansal, Aasthaa; Yu, Kaiyue; Glascock, Morgan; Kreizenbeck, Karma L.; Watabayashi, Kate; Wilson, Richa; Ittes, Annika; Bilgin Keciciler, Canan; Campinha-Bacote, Avrita; Yu, Wei; et al.
Abstract : 443 Background: Up to half of pts with cancer receiving systemic therapy have unplanned emergency department or hospital admission during treatment. ML41539 is a prospective observational study of an app to collect electronic patient-reported outcomes (ePROs) and a wearable biosensor (Samsung Galaxy Watch3) to evaluate the use of a remote monitoring system to improve symptom management and reduce unplanned admissions (ISRCTN25569053). Here, we report the initial feasibility and usability results for the ePRO app and biosensor. Methods: The study includes a vanguard phase (n = 32) to obtain early feedback on pt experience of the app and biosensor. After 2 weeks of continuous biosensor monitoring and daily ePRO reporting, 10 pts participated in semi-structured telephone interviews conducted by trained study staff. Open-ended questions addressed usability and technology-driven facilitators and barriers. Pts were also asked about ease of use and biosensor comfort on a 10-point Likert scale (higher scores reflected better usability and comfort). Transcripts were summarized using a FITTE-adapted framework and coded in ATLAS.ti 22.0.11.0. Coded data were summarized and consolidated into matrices to identify areas for improvement in future study phases. Results: Participants were approached until the target of 10 completed interviews was met. Respondents resembled the overall study population with regards to gender, race, ethnicity, age, and adherence to wearing the sensor and completing daily ePROs. For ease of use, the average rating among participants was 9 for the app (range 8.5-10) and 9.5 for the biosensor (range 7-10). Biosensor comfort was rated 7 on average (range 3-9). The most common words used to describe the app were "easy, " "simple, " and "straightforward." Sixty percent of pts said that the watch needed to be charged too often and that their experience could be improved by offering more sensor functions and allowing pts to view and track their ePRO responses and biometric data. Sixty percent of pts also supported using these technologies to monitor symptoms during cancer therapy, stating that it was a good idea or useful, especially if it prevented hospitalization or increased communication with their care team. Conclusions: Overall, pts reported positive experiences wearing the sensor and using the ePRO app to report their symptoms during the 2-week observation period. Ease of use was high for both the app and biosensor. A majority reported dissatisfaction with the battery life of the biosensor. Most stated that they would prefer more opportunities to interact directly with the devices and to monitor their own symptoms by viewing collected ePRO and biometric data. Building this type of functionality into the app and sensor for future study phases could help pts engage more with the devices and potentially improve adherence. Clinical trial information: ISRCTN25569053.